(untitled) (Research, Society and Development, 2020)
Objective: to describe a view of the nursing staff of a transitional hospital on the prevention and occurrence of falls in the elderly. Method: This is a qualitative, descriptive study carried out in a transitional hospital located in the city of Niterói - RJ, Brazil. Thirty-three nursing professionals participated in the study, of which there are seven nurses and twenty-six nursing technicians through semi-structured audio taped interviews that, after transcription, were submitted to Bardin’s thematic analysis. Results: after analysis, three categories emerged: the experience of professionals with falls; the specific knowledge of professionals about falls and the performance of professionals after the falls incident. Conclusion: It was identified that the professionals know preventive measures for falls but expressed the need for educational actions on protocols and scales for assessing the risk of falls in the elderly.